Limitations in daily activities and general perception of quality of life: Long term follow‐up in patients with anti‐myelin‐glycoprotein antibody polyneuropathy. Issue 3 (26th August 2019) - Campagnolo, Marta; Ruiz, Marta; Falzone, Yuri M.; Ermani, Mario; Bianco, Mariangela; Martinelli, Daniele; Cerri, Federica; Quattrini, Angelo; Salvalaggio, Alessandro; Castellani, Francesca; Comi, Giancarlo; Giannini, Fabio; et al.
Abstract: In this study, we assessed the modifications over time of daily activities and quality of life (QoL) in 32 subjects with anti‐myelin‐glycoprotein (MAG) antibody neuropathy. A widespread panel including clinical scores and patient‐reported questionnaires, in compliance of the terms by the International Classification of Functioning, Disability, and Health (ICF) of the World Health Organization (WHO), was employed at enrollment (T0) and at follow‐up evaluation (T1) after a mean interval of 15.4 ± 5.7 months. The Sensory Modality Sum score (SMS) at four limbs showed a significant worsening over time (mean score 27.2 ± 3.9 at T0 vs 25.7 ± 3 at T1 at upper limbs, P = .03; 20.5 ± 4.8 at T0 vs 18.6 ± 5.9 at T1 at lower limbs, P = .04). The Visual Analogue Scale (VAS) for pain significantly worsened at upper limbs at T1 (mean values 0.84 ± 1.95 at T0 vs 1.78 ± 2.6 at T1, P = .03). All the other tests did not show significant differences between T0 and T1. In the subgroup who underwent rituximab (15/32 treated before T0, 3/32 patients treated between T0 and T1 with median interval of 1 year), no significant differences were observed between T0 and T1. Despite the quite long follow‐up, statistical significance was not achieved either for the limited number of patients or for the lack of sensitive outcome measures. In our cohort, the significant worsening of the SMS and VAS after a median of 14 months can be considered as a reliable expression of the natural history of the disease, and suggest that these scales might represent possible outcome measures in anti‐MAG antibody neuropathy.